2022
DOI: 10.1063/5.0099786
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemical disorder on mechanical and thermal properties of multi-component rare earth zirconate pyrochlores (nRE1/n)2Zr2O7

Abstract: To explore the underlying mechanism of chemical disorder in high-entropy pyrochlores, ten rare earth zirconates ( nRE1/ n)2Zr2O7 ( n = 1, 2, and 4, RE = La, Nb, Sm, Eu, and Gd) are studied by using first-principles calculations. The mechanical and thermal properties are carefully analyzed with a special focus on local structural evolution and interatomic interaction. It is found that all three kinds of bond lengths increase linearly with lattice parameters whether the pyrochlore involves chemical disorder or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In this work, the mechanical and thermal properties (i.e., the elastic constants, bulk, shear and Young's moduli, and thermal conductivity) of (LaSmEuGd) 2 Zr 2 O 7 are lower than those of (NdSmEuGd) 2 Zr 2 O 7 . As La lacks f electrons and has large ionic radius, the bond length of (LaSmEuGd) 2 Zr 2 O 7 is longer than that of (NdSmEuGd) 2 Zr 2 O 7 , 36 which indicates the relatively weaker atomic interaction in this compound. Intuitively, it is believed that these mentioned earlier may be the critical points as the key to dominate the influence of chemical disorder on properties and performance for the high‐entropy pyrochlores.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In this work, the mechanical and thermal properties (i.e., the elastic constants, bulk, shear and Young's moduli, and thermal conductivity) of (LaSmEuGd) 2 Zr 2 O 7 are lower than those of (NdSmEuGd) 2 Zr 2 O 7 . As La lacks f electrons and has large ionic radius, the bond length of (LaSmEuGd) 2 Zr 2 O 7 is longer than that of (NdSmEuGd) 2 Zr 2 O 7 , 36 which indicates the relatively weaker atomic interaction in this compound. Intuitively, it is believed that these mentioned earlier may be the critical points as the key to dominate the influence of chemical disorder on properties and performance for the high‐entropy pyrochlores.…”
Section: Resultsmentioning
confidence: 96%
“…In recent decades, theoretical studies are widely adopted in pyrochlore investigations. [33][34][35][36] It can not only predict the thermal and mechanical properties of the materials Their structures, mechanical properties, and thermal properties at different temperatures are calculated. It is found that (ZrO 6 ) polyhedrons and phonon mean free path play major roles in the variation of mechanical properties and thermal properties with temperature, respectively.…”
Section: Ta B L E 1 Potential Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the correlation between the phonon scattering coefficient and the thermal conductivity is given by Eqs. ( 24) and ( 25) [74][75][76][77][78][79]:…”
Section: Thermal Conductivitymentioning
confidence: 99%